Study on the Construction of Water Environment Promotion Joint Control and Joint Regulation System in Plain River Network Area. Issue 1 (February 2021) - Xie, Chen; Pan, Xiaobao; Ding, Rui; Liu, Guoqing; Liu, Yang
Abstract: There are many river networks in Southeast plain cities of China, such as dense river network, many water projects, poor connectivity, strong pollution load into the river, and difficulty in regulation and control. The water environment problem of river network has become the bottleneck restricting the sustainable economic and social development of plain river network area. In order to improve the river water environment, it is very important to carry out reasonable intelligent regulation of regional river system. In view of the current situation that the water environment regulation is mainly based on manual operation and has not formed intelligent dispatching decision-making, this paper integrates the technology of water power and water quality joint control of urban river network, researches and develops the joint control and joint dispatching system of water environment improvement in plain river network area, and establishes a full coverage, full element three-dimensional monitoring and warning, dispatching and intelligent decision-making system, driven by monitoring data, with model as the core and remote control as the core with the goal of hydrodynamic, water level and water quality as the target, relying on the model cloud, the intelligent one click precise scheduling is realized.